The Nature of Democratic Regional Regulation Formation in Regional Government Administration - Iqram, Muh; Husen, La Ode; Hafidz, Ma’ruf; Razak, Askari (Journal of Cultural Analysis and Social Change, 2026)
The objectives of this research are to (1) determine, analyze, and explore the nature of substantively just regional regulations within the Indonesian legal system, particularly those related to tourism, and (2) determine, analyze, and examine the implementation of such substantively just regional regulations in the tourism sector. This study is classified as empirical legal research because it views law not only as a set of written norms or legislation but also as a social reality that operates within society, particularly in relation to the processes of formulating regional regulations that embody substantive justice. The findings indicate that the creation of substantively just regional regulations in the tourism sector requires a comprehensive approach that integrates collaboration among multiple stakeholders. Essential elements include the digitalization of micro, small, and medium enterprises (MSMEs) to enhance efficiency, the utilization of emerging technologies such as the metaverse to create innovative tourism experiences, the development of an investment climate conducive to economic recovery, and the recognition of indigenous community rights to cultural and environmental sustainability. To achieve effectiveness, such regulations must emphasize gender equity and inclusivity, reduce dependence on large corporations that may exacerbate inequality, and be supported by a robust legal framework, an efficient dispute resolution mechanism, and harmonized legal interpretations. By maintaining a balance among ecological, social, and economic dimensions, these regulations can serve as a foundation for sustainable and inclusive tourism development. The research recommends that the creation of fair and effective tourism regulations should adopt a data-driven approach, encourage active participation from local communities, and promote collaboration with the private sector to foster a sustainable investment environment. Effective implementation also requires strengthening law enforcement capacity through education and training, fostering community-based collaborative enforcement, and leveraging technology to monitor compliance. Future studies should focus on integrating sustainable policy frameworks and analyzing emerging challenges, including food security and climate resilience, to support the growth of an inclusive and sustainable tourism sector in Indonesia.